Pacing extremely old patients: who decides—the doctor, the patient, or the relatives?. Issue 2 (16th January 2004) - Sayers, G M; Bethell, H W L
Abstract : Decision making competence is not necessarily present or absent. In many cases it is partial or compromised. This applies especially to those over 80 years old, in whom the prevalence of dementia is high. Three patients who presented with indications for permanent pacemaker insertion are considered. One was apparently competent, one had partial competence, and one was clearly incompetent. In all three cases the closest relatives were opposed to decisions made by either the patient or the doctors. The three cases reflect the tension between doctors, patients, and relatives in situations where medical interests, individual interests, and familial interests conflict. The cases illustrate the type of problems encountered in clinical practice. The current legal position is reviewed.